2010
DOI: 10.1159/000294340
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Placental Protein 13 at Eleven to Thirteen Weeks in Chromosomally Abnormal Pregnancies

Abstract: Objective: To investigate whether the maternal serum concentration of placental protein 13 (PP13) is altered in chromosomally abnormal pregnancies and to examine the potential value of this placental protein in screening for aneuploidies at 11–13 weeks. Methods: The maternal serum concentration of PP13 at 11–13 weeks was compared in 536 euploid and 134 aneuploid pregnancies (trisomy 21: n = 49; trisomy 18: n = 28; trisomy 13: n = 19; Turner syndrome: n = 28; triploidy: n = 10). Results: Serum PP13, expressed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Nevertheless, it is noteworthy to mention these tests are just predictive of these pathologies and only more invasive tests, such as chorionic villus sampling, and amniocentesis, can assess the presence of chromosomal anomalies with more reliability (Chitayat et al, 2011). The other placental-related hormones, leptin (Hedley and Christiansen, 2008;Rizos et al, 2002) and PP13 (Akolekar et al, 2010;Koster et al, 2009) are not altered in Down's syndrome, and one study reported that the latter is decreased in the first trimester of trisomy 18 and 13 gestations (Akolekar et al, 2010).…”
Section: Chromosomal Anomaliesmentioning
confidence: 99%
“…Nevertheless, it is noteworthy to mention these tests are just predictive of these pathologies and only more invasive tests, such as chorionic villus sampling, and amniocentesis, can assess the presence of chromosomal anomalies with more reliability (Chitayat et al, 2011). The other placental-related hormones, leptin (Hedley and Christiansen, 2008;Rizos et al, 2002) and PP13 (Akolekar et al, 2010;Koster et al, 2009) are not altered in Down's syndrome, and one study reported that the latter is decreased in the first trimester of trisomy 18 and 13 gestations (Akolekar et al, 2010).…”
Section: Chromosomal Anomaliesmentioning
confidence: 99%
“…One of those markers is placental protein 13 (PP13) which plays an important role in the implantation and modelling of foetal-maternal blood spaces between placenta and endometrium. PP13 is produced by the placenta, which is hampered in trisomic pregnancies, and was found to be decreased in DS pregnancies and, to greater extent, in trisomy 18 and 13 pregnancies (Akolekar et al, 2010. Serum concentrations of a disintegrin and metalloprotease 12 (ADAM12) and placental growth factor (PlGF) are also decreased in DS pregnancies , Zaragoza et al, 2009.…”
Section: Proteomics Techniques To Identify New Screening Markers For mentioning
confidence: 99%
“…Recently, several studies have been performed in which new potential screening markers for Down syndrome were individually measured. A disintegrin and metalloprotease 12 (ADAM12), placental protein 13 (PP13) and placental growth factor (PlGF) have been shown to be decreased in Down syndrome pregnancies2–6. Moreover, total hCG, which is a screening marker for Down syndrome in the second trimester of pregnancy7, has also been reported to be increased in the first trimester in Down syndrome pregnancies8.…”
Section: Introductionmentioning
confidence: 99%